Teaching English by Using Andragogy Approach for EFL Students - Via Armu Manangsa; Paidi Gusmuliana; Eka Apriani (Journal of English Education and Teaching, 2020)
This study aims to find out whether the English lecturer study program, in other words, has applied andragogy as teaching to people who have been considered adults. The lecturer uses andragogy as a good guide in conveying a knowledge that is focused on student experience, student needs and related to student personalization. Andragogy is instruction for adults to be more focused on the process and to reduce less on the content taught in learning. This article adopts the instruments of the victor cx wang article published in 2015. These findings indicate that lecturers are more directed towards students who become students-centered which are characterized by group discussions, lecturers only direct through lectures and encourage students to dialogue. This teaching method is in line with teaching andragogy which directs adult students to be independent in learning.